LFR Physically and Genetically Interacts With SWI/SNF Component SWI3B to Regulate Leaf Blade Development in Arabidopsis - Lin, Xiaowei; Yuan, Can; Zhu, Bonan; Yuan, Tingting; Li, Xiaorong; Yuan, Shan; Cui, Sujuan; Zhao, Hongtao (Frontiers in Plant Science, 2021)
Leaves start to develop at the peripheral zone of the shoot apical meristem. Thereafter, symmetric and flattened leaf laminae are formed. These events are simultaneously regulated by auxin, transcription factors, and epigenetic regulatory factors. However, the relationships among these factors are not well known. In this study, we conducted protein-protein interaction assays to show that our previously reported Leaf and Flower Related (LFR) physically interacted with SWI3B, a component of the ATP-dependent chromatin remodeling SWI/SNF complex in Arabidopsis. The results of truncated analysis and transgenic complementation showed that the N-terminal domain (25-60 amino acids) of LFR was necessary for its interaction with SWI3B and was crucial for LFR functions in Arabidopsis leaf development. Genetic assay results showed that the artificial microRNA knockdown lines of SWI3B (SWI3B-amic) had a similar upward-curling leaf phenotype with that of LFR loss-of-function mutants. ChIP-qPCR assay was conducted to show that LFR and SWI3B co-targeted the promoters of YABBY1/FILAMENTOUS FLOWER (YAB1/FIL) and IAA carboxyl methyltransferase 1 (IAMT1), which were misexpressed in lfr and SWI3B-amic mutants. In addition, the association between LFR and the FIL and IAMT1 loci was partly hampered by the knockdown of SWI3B. These data suggest that LFR interacts with the chromatin-remodeling complex component, SWI3B, and influences the transcriptional expression of the important transcription factor, FIL, and the auxin metabolism enzyme, IAMT1, in flattened leaf lamina development.